Cognitive Alexithymia Mediates the Association Between Avoidant Attachment and Interpersonal Problems in Patients With Somatoform Disorder. Issue 6 (17th August 2016) - Koelen, Jurrijn A.; Eurelings-Bontekoe, Liesbeth H.M.; Kempke, Stefan
ABSTRACT: Patients with somatoform disorder (SFD) are characterized by the presence of chronic physical complaints that are not fully explained by a general medical condition or another mental disorder. Insecure attachment patterns are common in this patient group, which are often associated with interpersonal difficulties. In the present study, the mediational role of two types of alexithymia and negative affectivity (NA) was examined in the association between attachment styles and interpersonal problems in a group of 120 patients with SFD. Patients were requested to fill out several self-report questionnaires for the assessment of attachment strategies, alexithymia, NA, and interpersonal problems. Cognitive alexithymia (i.e., the inability to identify and verbalize emotions) mediated the relationship between avoidant attachment patterns and interpersonal problems, even after controlling for NA. Preliminary findings also suggested that NA acted as a moderator of the mediator cognitive alexithymia. These results have important implications for clinical practice, as this study clearly shows that interpersonal problems do not automatically follow from insecure attachment strategies, but are contingent upon alexithymic features. It is recommended to target alexithymic features in patients with SFD, particularly in the context of negative emotions. Therefore, cognitive alexithymia may be an important therapeutic focus, specifically in the treatment of avoidant ptients with SFD.